Andrographolide inhibits HMGB1‐induced inflammatory responses in human umbilical vein endothelial cells and in murine polymicrobial sepsis. (24th March 2014) - Lee, W.; Ku, S.; Yoo, H.; Song, K.; Bae, J.
Abstract Aim Nuclear DNA‐binding protein high‐mobility group box 1 (HMGB1) protein acts as a late mediator of severe vascular inflammatory conditions, such as septic shock, upregulating pro‐inflammatory cytokines. Andrographolide (AG) is isolated from the plant of Andrographis paniculata and used as a folk medicine for treatment of viral infection, diarrhoea, dysentery and fever. However, the effect of AG on HMGB1‐induced inflammatory response has not been studied. Methods Firstly, we accessed this question by monitoring the effects of post‐treatment AG on lipopolysaccharide (LPS) and caecal ligation and puncture (CLP)‐mediated release of HMGB1 and HMGB1‐mediated regulation of pro‐inflammatory responses in human umbilical vein endothelial cells (HUVECs) and septic mice. Results Post‐treatment AG was found to suppress LPS‐mediated release of HMGB1 and HMGB1‐mediated cytoskeletal rearrangements. AG also inhibited HMGB1‐mediated hyperpermeability and leucocyte migration in septic mice. In addition, AG inhibited production of tumour necrosis factor‐α (TNF‐α) and activation of AKT, nuclear factor‐κB (NF‐κB) and extracellular‐regulated kinases (ERK) 1/2 by HMGB1 in HUVECs. AG also induced downregulation of CLP‐induced release of HMGB1, production of interleukin (IL) 1β/6/8 and mortality. Conclusion Collectively, these results suggest that AG may be regarded as a candidate therapeutic agent for the treatment of vascular inflammatory diseases via inhibition of the HMGB1 signalling pathway.